ANALISIS PENGARUH VARIASI SUDUT KEMIRINGAN PANEL TERHADAP DAYA KELUARAN PANEL SURYA - Sulanjari Sulanjari; Joko Setiyono; Muhammad Adha Rosyahna; Agustina Dyah Setyowati; Ade Irawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The purpose of this study was to determine the effect of the solar panel angle of a 50 wp solar panel on the output power with a variation of the angle of 200, 300, and 400. Data collection was repeated 3 times using drying time or heating solar cell panels for 6 hours (09.00-15.00 WIB) with intervals 30 minutes. The results of testing the installation of a solar power plant it can be concluded that the largest output power is on day 1 with a slope angle of 400 at 13:00 WIB with a value of 53.07 Watt, and the smallest output power is on day 2 with a slope angle of 300 at 15:00 WIB with a value of 3.03 Watt. And the greatest efficiency value is on day 1 with a slope angle of 200 at 12:30 WIB with a value of 17.52% and for the smallest efficiency value, namely on day 2 with a slope angle of 400 at 14:00 WIB with a value of 2 ,54%.Keywords: Solar panel angel, 50 wp, solar cell, output power, efficiency.